CHARACTERIZATIOS and PROPERTIES of b-T1/2-SPACES - Hussain, Adea; Abd Alatif, Ali (Iraqi Journal of Science, 2024)
In this paper we introduce a new class of spaces, namely b-T1/2-space, which isstrictly between b-T0 and b-T1 spaces, and weaker than Tgs-space. Several properties andcharacterizations for this space are investigated.